Nexus Texas - Contemporary Arts Museum, Houston (Houston : Contemporary Arts Museum Houston, 2007)
Allen, Sterling ; Bellini, Roberto ; Blakemore, Amy ; Boyd, Justin ; Cabrera, Margarita ; Stefano, Augusto Di ; Hewitt, Leslie ; Kelley, Lauren ; Lee II, El Franco ; Patterson, Richard ; Slocum, Paul ; Smith, Cauleen ; Smith, George ; Smith, Michael ; Sweeney, Gary ; Zilm, Jeff
biog., ind. tent., gr. tent., bibliog. p. 83-93
Engels
Exhibition. Nexus Texas. Houston. Contemporary Arts Museum Houston. 2007-08-18. 2007-10-21
boek